A (Simplified) Biogeochemical Numerical Model to Predict Saturation, Porosity and Permeability During Microbially Induced Desaturation and Precipitation. Issue 1 (9th January 2023) - Wang, Liya; van Paassen, Leon; Pham, Vinh; Mahabadi, Nariman; He, Jia; Gao, Yunqi
Abstract: Microbially Induced Desaturation and Precipitation (MIDP) through denitrification is an emerging ground improvement method in which indigenous nitrate reducing bacteria are stimulated to introduce biogas, biominerals and biomass in the soil matrix. In this study, a numerical model is developed to evaluate the effect of biogas, biominerals and biomass on the hydraulic properties of soils treated with MIDP. The proposed model couples the biochemical conversions to changes of porosity and water saturation and predicts changes in permeability through two separate power law equations. Experimental studies from the literature are used to calibrate the model. Comparing the results with other studies on bioclogging or biomineralization in porous media reveals that the combined production of biogas, biomass, and biominerals results in efficient clogging, in the sense that only a small amount of products leads to a substantial permeability reduction. Based on this comparison, the authors postulate that biogenic gas bubbles preferably form within the larger pore bodies. The presence of biogenic gas in the larger pore bodies forces calcium carbonate minerals and biomass to be formed mainly at the pore throats. The interaction between the different phases results in more efficient clogging than observed in other studies which focus on a single product only. Key Points: A model predicts the combined effect of bioproducts on soil permeability treated by Microbially Induced Desaturation and Precipitation (MIDP) To simulate the permeability reduction by MIDP, the effects of the different products need to be treated separately The interaction between the different phases of products in MIDP may result in more efficient clogging than each single phase alone